Improved Refractive Index Sensitivity Utilizing Long-Period Gratings with Periodic Corrugations on Cladding. (27th June 2012) - Lim, Anthony; Ji, Wen Bin; Tjin, Swee Chuan
Abstract : A new structure of Long-Period Gratings (LPGs) sensor is introduced as a sensitive ambient RI sensor. This structure consists of creating periodic corrugations on the cladding of the LPG. The experimental results show that this LPG structure has good performances in terms of linearity and sensitivity and serves as a highly sensitive and cost-effective sensor. It also has the advantage of portability as the corrugation can also serve as the reservoir for the specimen collection to be tested.